Influence of empathy on work alienation among Chinese nurses during the COVID-19 pandemic: The mediating effect of ego depletion - Cui, Yi; Yang, Tianqi; Zhang, Man; Liu, Na; Liu, Qin; Zhang, Lanfang; Zhang, Lihua; Yang, Haoshuang; Zhang, Yinling (Frontiers in Psychology, 2023)
Background Nurses’ work alienation has become increasingly serious due to the increase in workload and risk during the coronavirus disease 2019 (COVID-19). However, no studies have investigated the link between empathy, ego depletion, and work alienation among Chinese nurses. The present study aimed to evaluate Chinese nurses’ empathy, ego depletion, and work alienation and to examine whether nurses’ ego depletion mediates the relationship between empathy and work alienation. Methods This was a descriptive, cross-sectional study involving 353 nurses from Shaanxi. The Jefferson Scale of Empathy-Health Professionals, Self-Regulating Fatigue Scale and Work Alienation Questionnaire were used to collect data through an online survey. Structural equation modeling was conducted to analyze the mediating model. Results Work alienation was negatively correlated with empathy (r = −0.305, p < 0.01) and positively correlated with ego depletion (r = 0.652, p < 0.01). Empathy was negatively correlated with ego depletion (r = −0.325, p < 0.01). Empathy can directly predict work alienation (β = −0.263, p < 0.01), while ego depletion has a mediating effect between empathy and work alienation (β = −0.309, p < 0.01), and the mediating effect accounts for 54.02% of the total effect. Conclusion Nurses’ work alienation was at a moderate-to-high level. Improving empathy can reduce work alienation through less ego depletion. Nursing managers should discover nurses’ work alienation as soon as possible. Interventions to improve empathy can help replenish nurses’ psychological resources, thereby reducing ego depletion and work alienation.